Conversion of polyethylene terephthalate waste into high-yield porous carbon adsorbent via pyrolysis of dipotassium terephthalate. (1st May 2023) - Efimov, M.N.; Vasilev, A.A.; Muratov, D.G.; Kostev, A.I.; Kolesnikov, E.A.; Kiseleva, S.G.; Karpacheva, G.P.
Graphical abstract: Highlights: Approach of PET waste conversion into high-yield porous carbon was proposed. KOH hydrolysis of PET dissolved in DMSO forms dipotassium terephthalate. This technique provides mild conditions of hydrolysis (150 °C, atm pressure, 10 min). Dipotassium terephthalate helps to keep a carbon residue until 850 °C pyrolysis. PET-derived porous carbon has MB adsorption value of 443 mg g −1 . Abstract: A method for conversion of polyethylene terephthalate (PET) waste into porous carbon material is proposed. The recycling of PET bottle waste includes the stages of low-temperature hydrolysis of the polymer and subsequent pyrolysis at 800 °C. To provide PET hydrolysis at ∼150 °C and atmospheric pressure, the polymer was pre-dissolved in dimethyl sulfoxide and then an aqueous solution of potassium hydroxide was added. The potassium terephthalate formed as a result of the alkaline hydrolysis of PET allows the carbon-containing precursor to be preserved for further activation to temperatures beyond 600 °C. The proposed method leads to the formation of a porous carbon material, increasing the yield of carbon residue to 25 wt%, which is higher compared to the yield of carbon residue in the direct pyrolysis of PET. The obtained porous carbon is characterized by graphite-like structure and specific surface area of ∼1100 m 2 g −1 . It has been shown that PET-derived carbon material can be used to remove pollutants from aqueous media. The adsorption properties of the carbon material were demonstrated by adsorption of methylene blue from an aqueous solution. The capacity of the carbon material was found to be 443 mg g −1 .